PENGELOLAAN PAJAK KENDARAAN BERMOTOR DI PROVINSI MALUKU UTARA - S. Awal, Fridayati; Hadi Sirat, Abdul; Hadady, Hartaty (Penerbit Lafadz Jaya, 2025)
The purpose of the study was to analyze the effectiveness and efficiency of Motor Vehicle Tax (PKB) management in North Maluku Province. This study uses a qualitative descriptive method through case studies, in-depth interviews, and secondary data analysis for the period 2019–2023. The results of the study indicate that in general the realization of PKB revenue in the three study areas is included in the effective to very effective category, especially Samsat Ternate City and Tidore City. However, the realization of arrears is still relatively ineffective, especially in North Halmahera Regency. In terms of efficiency, all UPTDs showed efficient performance with consistent collection costs at 20%. Meanwhile, the contribution of fines to PKB revenue is still low, especially for annual taxes. The main inhibiting factors include low taxpayer awareness, limited operational facilities, document constraints such as BPKB, and limited technology. However, programs such as Mobile Samsat, e-Samsat, and Sidola Batagi have begun to have a positive impact on increasing tax compliance and revenue. This study recommends optimizing service digitalization, increasing public education, and synergy between agencies as strategic steps to improve PKB management in North Maluku.